2015
DOI: 10.1016/j.fertnstert.2015.07.241
|View full text |Cite
|
Sign up to set email alerts
|

Male partner sexual abstinence less than 2 or greater than 7 days is not associated with increased aneuploidy rate

Abstract: was a significant decline in initial sperm count (p < 0.001), sperm motility (p < 0.001), total count (p < 0.001) and total motile count (p < 0.001) during the period 2003-2013. There was no significant change in semen volume (p ¼ 0.2). Following cryopreservation, the mean post-thaw motility significantly (p < 0.001) decreased with time. There was a significant decline in age (p trend ¼ 0.003) and alcohol use (p trend ¼ 0.005), as well as an increase in college GPA (p trend ¼ 0.02). However, BMI (p trend ¼ 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a recent study, Gingold et al. () reported that SAP beyond the range recommended by the WHO was not associated with an increased aneuploidy rate. Additionally, in our previous study, we found no significant differences between 2–4 and 5–7 days of SAP on the rates of fertilisation, top‐quality embryos on day 3 and pregnancy outcomes in fresh ET after ICSI (Lee et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, Gingold et al. () reported that SAP beyond the range recommended by the WHO was not associated with an increased aneuploidy rate. Additionally, in our previous study, we found no significant differences between 2–4 and 5–7 days of SAP on the rates of fertilisation, top‐quality embryos on day 3 and pregnancy outcomes in fresh ET after ICSI (Lee et al., ).…”
Section: Discussionmentioning
confidence: 97%